Assessment of the Constructionality of the Structure in the Assembly Processes - Matuszek, Jozef; Seneta, Tomasz; Dulina, Luboslav; Bigosova, Eleonora (Communications - Scientific Letters of the University of Zilina, 2021)
The paper presents the methodology of designing the production process of a new product from the point of view of the criterion of the assembly operations technology (Design for Assembly - DFA) in the automotive industry. The article describes methods and techniques used during the implementation of a new product into production. The impact of the methods on improving the assembly technology of a complex product is described. Suggestions for improving for unit and small series production are presented.
Keywords: production process design; construction manufacturability; unit; small-lot production